Role of cannabis in digestive disorders. Issue 2 (February 2017) - Goyal, Hemant; Singla, Umesh; Gupta, Urvashi; May, Elizabeth
Abstract : Cannabis sativa, a subspecies of the Cannabis plant, contains aromatic hydrocarbon compounds called cannabinoids. [INCREMENT] 9 -Tetrahydrocannabinol is the most abundant cannabinoid and is the main psychotropic constituent. Cannabinoids activate two types of G-protein-coupled cannabinoid receptors: cannabinoid type 1 receptor and cannabinoid type 2 receptor. There has been ongoing interest and development in research to explore the therapeutic potential of cannabis. [INCREMENT] 9 -Tetrahydrocannabinol exerts biological functions on the gastrointestinal (GI) tract. Cannabis has been used for the treatment of GI disorders such as abdominal pain and diarrhea. The endocannabinoid system (i.e. endogenous circulating cannabinoids) performs protective activities in the GI tract and presents a promising therapeutic target against various GI conditions such as inflammatory bowel disease (especially Crohn's disease), irritable bowel syndrome, and secretion and motility-related disorders. The present review sheds light on the role of cannabis in the gut, liver, and pancreas and also on other GI symptoms, such as nausea and vomiting, cannabinoid hyperemesis syndrome, anorexia, weight loss, and chronic abdominal pain. Although the current literature supports the use of marijuana for the treatment of digestive disorders, the clinical efficacy of cannabis and its constituents for various GI disorders remains unclear.